1992
DOI: 10.1016/0014-5793(92)81470-7
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the Na,K‐ATPase by modification of Lys‐501 with 4‐acetamido‐4′‐isothiocyanatostilbene‐2,2′‐disulfonic acid (SITS)

Abstract: The sodium pump or Na,K-ATPase, maintains the Na ÷ and K" gradients across eukaryotic cell membranes at the expense of ATP. Incubation of purified canine renal Na,K-ATPase with 4-acetamido-4'-isothioeyanatostilbene.2,2'-disulfoni¢ acid (SITS) inhibited tile ATPase activity. Both the labeling of the protein and the loss of ATPase acti~,ity were prevented by co-incubation with ADP (acting as an ATP analog) or KCI, Only the a-subunit was labeled by SITS, The ~t.subunit fi'om ll~e inhibited ellzymc was extensively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 15 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…In regard to Na-KATPase inhibition, DIDS and SITS were considered to be ineffective when applied to the exterior of intact cells because they do not readily penetrate the plasma membrane. This reasoning was based on the notion that their principle mechanism of action was a direct inhibitory effect caused by interaction with a Lys residue on the cytoplasmic portion of P-type ATPases (27,38). In the present study we show evidence that DIDS is able to cause Na-K-ATPase inhibition in ocular nonpigmented ciliary epithelium (NPE) by a mechanism that is associated with SFK activation.…”
Section: Discussionmentioning
confidence: 84%
“…In regard to Na-KATPase inhibition, DIDS and SITS were considered to be ineffective when applied to the exterior of intact cells because they do not readily penetrate the plasma membrane. This reasoning was based on the notion that their principle mechanism of action was a direct inhibitory effect caused by interaction with a Lys residue on the cytoplasmic portion of P-type ATPases (27,38). In the present study we show evidence that DIDS is able to cause Na-K-ATPase inhibition in ocular nonpigmented ciliary epithelium (NPE) by a mechanism that is associated with SFK activation.…”
Section: Discussionmentioning
confidence: 84%
“…Formation of a cross‐link by H 2 DIDS (and presumably DIDS) had been the major source of the difficulty in determining its site of modification in earlier experiments. Previous work from our laboratory, 14 demonstrated that the single isothiocyano‐substituted stilbene, SITS, was an irreversible inhibitor of the Na,K‐ATPase. Like DIDS, SITS inactivation was completely preventable by the presence of either ATP or low K + .…”
Section: Atp Binding and The Cytoplasmic Loopmentioning
confidence: 94%
“…The segment of this loop located between D369 and G502 is particularly interesting. It has been observed that a variety of aryl isothiocyanates, including NIPI, 13 SITS, 14 and FITC, 17,18 covalently label K501 in the absence of ATP but not in its presence, consistent with K501 residing in or close to the ATP site. Also, the photoaffinity ATP analogs, 2‐azido‐ATP and 8‐azido‐ATP, have been shown to modify K480 and G502, respectively; these modifications are eliminated by the simultaneous presence of ATP 18 .…”
Section: Atp Binding and The Cytoplasmic Loopmentioning
confidence: 97%
“…The MIANS-labeled proteins were visualized by illumination with a long wave UV lamp. Only the ␣-subunit was labeled in all cases where MIANS was present (lanes 2-6) hydro-4,4Ј-DIDS (5, 24), 4-acetamido-4Ј-isothiocyanatostilbene-2,2Ј-disulfonate (25), and fluorescein isothiocyanate (6), compounds that also inactivate Na,K-ATPase in an ATP-protectable manner and whose sites of action have been localized to the ATP-binding loop (i.e. K501).…”
Section: Figmentioning
confidence: 99%